IDENTIFIKASI BERAT, DIAMETER, DAN TEBAL DAGING BUAH MELON (Cucumis melo, L.) KULTIVAR ACTION 434 TETRAPLOID AKIBAT PERLAKUAN KOLKISIN - Y. Ulung Anggraito (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Indonesian farmers are very dependence on certificated seed from another countries. In the other side the natural resources and men powers very abundance. For these reason it is properly developed the research in agriculture sector, especially on plants breeding. It can be hoped that in the future the dependence on certificated seed from another countries can be minimized. The objective of this research were: (1) to find out the concentration and dipping period which is effective to induce polyploid in musk melon plant, (2) identify the weight, diameter, dan flesh thickness of tetraploid musk melon as result of colchicines treatment. The sample of this research was Action 434 musk melon cultivar, product of Chia-Thai Seed, Thailand. The number of sample was 480 plants, which plants on field randomly. There were four colchicines concentration as an independent variable: 0.0%, 0.05%, 0.10% and 0.2%. The dipping period were 12, 16, 20, and 24 hours for each concentration respectively. Completely Random Design was used in three replications. Data measurement were analyzed with Two Way ANOVA, DMRT, and LSD. From this research can be concluded that: (1) 0.2 % colchicine is the most effective concentration to induce polyploid on musk melon, with dipping period effective varied from 16–24 hours, (2) there are changes in weight, diameter, and flesh thickness characters, with the increased tendency of each character in definite norm.